Efektivitas Wakaf Produktif sebagai Instrumen Keuangan Sosial Islam: Perspektif Hukum Islam - Ahmad Masyhadi; Moh. Sahlul Khuluq; M. Mar’il Farochi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
Productive waqf has become a significant social finance instrument in supporting economic development and social welfare among Muslims. This study aims to evaluate the effectiveness of productive waqf as an Islamic social financial instrument from the perspective of Islamic law. This study uses a qualitative approach with a descriptive-analytical method. The results of the study show that productive waqf, which is managed professionally and in accordance with sharia principles, has great potential to make a significant contribution to social welfare. This study concludes that productive waqf has great potential to become a source of sustainable funding that supports social, educational, and health programs, as well as empowering the community's economy